Salubrious effects of a vermiculite–cellulose‐based bionanocomposite on oxidative stress indices and histomorphology of male Wistar rats. (31st October 2019) - Otuechere, Chiagoziem A.; Adewuyi, Adewale; Oluwabayo, Tanitoluwa; Afolayan, Folashade; Avwioroko, Oghenetega; Abazuh, Uche
Abstract: There is a current interest from the food packaging, biomedical and agricultural sectors in hybrid materials formed from clays and natural polymeric compounds. However, research investigating the toxicity of vermiculite–cellulose nanocrystal (VERN) hybrid on the testes of Wistar rats is rare. Twenty rats, divided into control and treatment groups, were orally administered distilled water, 5, 10, and 20 mg/kg bw VERN daily for two consecutive weeks. At the termination of experiments, the testicular organo‐somatic index, superoxide dismutase, catalase, and gamma‐glutamyl transferase activities were not significantly changed by VERN relative to the controls. Contrarily, myeloperoxidase, glutathione peroxidase, and malondialdehyde levels were depleted in the testes of treated rats. Moreso, VERN increased follicle‐stimulating and luteinizing hormones, and decreased testosterone levels at the 20 mg/kg dose. Histology of the testes revealed healthy looking Leydig cells at the doses of 5 and 10 mg/kg VERN. Overall, these results indicate that oral exposure of VERN was not overly deleterious to the redox and structural histoarchitecture in the testes of rats.